تسوية المنازعات الضريبية في التشريع الجزائري - يزيد الصالح-جميات محمد الصالح (جامعة المسيلة, 2021)
Tax litigations can be distinguished from others by their particular character. Conflict outbreak is mainly a matter of accepting the tax imposed by the tax administration. When it clearly seems that there has been an error related to the base assessment or to tax collection, and before the taxpayer resorts to the board of appeal or to the specialized tribunal, he must lodge a complaint with the tax administrator to explain his concern, either the litigation is related to the base assessment or to its collection. The legislator has clearly defined the time period for filling of tax claim according to the nature of the litigation. He set out formal and objective conditions which are nearly common in terms of plaints linked to base assessment and those related to debts collection, according to articles 73 and 75 of the fiscal procedures law in force and articles 153 and 153a of the same law. Regardless of the subject matter of the litigation, be it the base or the collection, this does not interrupt the payment process neither the right of the tax administration to initiate the collection procedure. Consequently, the legislator has granted to the taxpayer a legal right to postpone payment when it comes to litigation related to the base, and a request for the extension of debts collection. Once the appeal meets all conditions and procedures, it is the role of the tax administration to solve this appeal, with the participation of other organs when studying these situations. Moreover, the tax Director may also reject the claim witnessing an error in form, and the role of the inspector here is to inform the concerned director of these errors. In this case, the tax collector takes all necessary precautions encouraging the taxpayer to provide guarantees to make sure about the collection by the tax direction which will be postponed, so that the competent tax director makes the suitable decision, either by accepting the appeal, or by refusing it in whole or in part. In this Abstract Résumé 127 case, if the litigation is related to the assessment of the tax base, the taxpayer may recourse to the competent commission as an alternative to resolve tax litigations. There are three types of these commissions, each of which is mainly concerned by the financial index of the tax amount. Appeal procedures before these commissions are also subject to several conditions, such as: deadlines for appeal. Decisions of these commissions satisfying conflict parties may come to fruition to avoid going to court and following complex contentious proceedings. The judicial litigation here is relevant to the competence of the administrative judicial power, pursuant to the article 804-1 from the Code of Civil and Administrative Procedure, subject to appeal before the council of the state, specialized in both and last instances of annulment appeals. To interpret the equality shaped against administrative actions issued from central administrative authorities, national public institutions and national professional organizations. Except for affairs linked to a fiscal offence, there are two cases the administrative judge can witness through the fiscal offence. The case which intervenes after the denial of the claim introduced by the taxpayer before the tax administration. And the appeal instituted by the tax administration against decisions of appeal commissions. The legislator has fixed conditions of litigations in taxation covered in the tax procedure code, such as: the prior signature, the signature of the application instituting proceedings and trial filling dates. When all the conditions have been satisfied, the tax litigation commences on the date of the first registration on the administrative tribunal registry. After informing the president of the administrative tribunal about the content of the application instituting proceedings, he will be assigned to name the judicial staff of judges who will rule on the affair. The tribunal opens investigations and to establish evidences related to this dispute. If there are any anterior relations between the tax administration and the taxpayer, that would facilitate the process of establishing evidences and allow the appellant to generate evidences supporting his claims. According to the article 85 from the Algerian tax Abstract Résumé 128 procedure code, complementary investigation about taxation, the re-examination of the investigation or the expertise are the only procedures of investigation that can be ordered after cancelling the initial investigation. Afterwards, the sentence granted on the litigation by the administrative tribunal pursuant to the civil and administrative procedure code. Once the verdict is rendered, it is vested with the executive and unstoppable power by the period of appeal before the council of the state. The sentence is communicated to the taxpayer or the tax administration by the bailiff or by the administrative tribunal’s clerk in exceptional cases. The appeal before the council of the state is one of the most important actions to be taken against the sentence rendered by administrative tribunals. Once the decision of the council of the state is announced, the sentence becomes final. It will be notified by a registered letter to the lawyer who handled the litigation as well as the lawyer on behalf of the tax administration. Considering that decision rendered by the council of the state are final, they are not subject to appeal except for purposes of rectification of error or an application for review. Otherwise, the sentence becomes final and is vested with the authority.
Keywords: المنازعات -الضريبية